Pengaruh Profitabilitas Terhadap Nilai Perusahaan Dimediasi Corporate Social Responbility Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia - Muhammad Syahrul Ramadani; Rida Perwita Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This consider points to test whether productivity influences company esteem interceded by Corporate Social Duty in mining companies recorded on the Indonesia Stock Trade. The populace of this think about are coal sub-sector mining companies recorded on the Indonesia Stock Trade amid 2018-2021. The testing method utilized purposive examining gotten 25 companies with 100 tests of watched information. Strategies of information examination utilizing different straight relapse examination. The information utilized is auxiliary information and employments a information collection strategy, to be specific a documentation consider. The information utilized in this ponder are budgetary report information and yearly reports by mining companies within the coal sub-sector gotten from the Indonesian Stock Trade site (https://www.idx.co.id). The comes about appeared that benefit had no critical impact on firm esteem, benefit had a noteworthy impact on Corporate Social Obligation. Corporate Social Obligation has no critical impact on firm esteem. Corporate Social Duty can intercede benefit with company esteem. Keywords: Profitability,The Value Of The Company, Corporate Social Responsibility.